Homomeric interactions between transmembrane proteins of Moloney murine leukemia virus. - Li, X (1996)
We have studied homomeric interactions between transmembrane proteins (TM) of the Moloney murine leukemia virus envelope using the Saccharomyces cerevisiae two-hybrid system. TM interacts strongly with itself but not with various control proteins. Deletional and mutational analyses indicated that the putative leucine zipper motif in the extracellular domain of TM is essential and sufficient to mediate the binding. The first three repeats of the leucine zipper-like motif are the most important in mediating the interaction. The TM-TM interaction detected in this system may play a role in several stages of viral replication.